1971
DOI: 10.1037/h0031192
|View full text |Cite
|
Sign up to set email alerts
|

Amnesic effects in short-term memory.

Abstract: A first study, free recall, showed that the von Restorff effect could be produced by the interpolation of a photograph of nude human beings at Serial Position 8 in a 15-item list consisting of line drawings of familiar objects. This effect was accompanied by a retrograde amnesia at the two serial positions immediately preceding the interpolated item. A substantial anterograde amnesia resulted from the nude photograph, affecting the 6 following positions. A second study presented 5s a recognition task. Lists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 4 publications
4
76
3
Order By: Relevance
“…These typically either involve sequences with just one arousing item (Hurlemann et al, 2005;Strange et al, 2003;Schmidt, 2002;Erdelyi & Blumenthal, 1973;Detterman & Ellis, 1972;Ellis et al, 1971;Runcie & O'Bannon, 1977;MacKay et al, 2004) or rapid serial visual presentation without responses required from the participants until the end of the list (Hadley & MacKay, 2006). The current findings suggest that this type of arousal-based interference seen for item memory will not extend to item-location conjunction memory.…”
Section: How These Findings Contrast With Other Effects Of Emotionmentioning
confidence: 55%
See 1 more Smart Citation
“…These typically either involve sequences with just one arousing item (Hurlemann et al, 2005;Strange et al, 2003;Schmidt, 2002;Erdelyi & Blumenthal, 1973;Detterman & Ellis, 1972;Ellis et al, 1971;Runcie & O'Bannon, 1977;MacKay et al, 2004) or rapid serial visual presentation without responses required from the participants until the end of the list (Hadley & MacKay, 2006). The current findings suggest that this type of arousal-based interference seen for item memory will not extend to item-location conjunction memory.…”
Section: How These Findings Contrast With Other Effects Of Emotionmentioning
confidence: 55%
“…A number of studies have shown that arousing stimuli can interfere with memory for spatially or temporally nearby neutral items (Bornstein, Liebel, & Scarberry, 1998;Detterman & Ellis, 1972;Ellis et al, 1971;Erdelyi & Blumenthal, 1973;Hadley & MacKay, 2006;Hurlemann et al, 2005;Johnson et al, 2005;MacKay et al, 2004;Miu, Heilman, Opre, & Miclea, 2005;Runcie & O'Bannon, 1977;Schmidt, 2002;Strange, Hurlemann, & Dolan, 2003). Although some of these studies used very rapid presentation, item memory impairment for temporally adjacent items also has been found with up to three or four seconds between the arousing and neutral items (Detterman & Ellis, 1972;Hurlemann et al, 2005;Runcie & O'Bannon, 1977) and sometimes even for items appearing six seconds after an arousing item (Schmidt, 2002).…”
mentioning
confidence: 99%
“…The results are less clear with respect to what aspects of memory for an emotional event are enhanced. Some researchers have reported suppressed memory for surrounding or peripheral information (N. R. Ellis et al, 1971;Kaplan & Pascoe, 1977;Loftus & Bums, 1982), whereas other researchers have reported enhanced memory for the context of the event (Bohannon, 1988;Brown & Kulik, 1977;Christianson, 1989;Heuer & Reisberg, 1990). The effects of emotion on memory are further complicated by the fact that these effects are to some extent state-dependent (e.g., Bower, 1981;Clark et al, 1983), are influenced by the strength of the emotional response (H. C. Ellis, 1985), and are asymmetrical for positive and negative moods (Isen, 1985).…”
Section: Relatedmentioning
confidence: 99%
“…In addition, recall and recognition of pictures following the nude were suppressed. Unfortunately, correct recall and recognition performance in the N. R. Ellis et al, (1971) study could be based simply on the memory that a nude was presented. Memory for specific details in the pictures was not assessed.…”
Section: Emotional Distinctivenessmentioning
confidence: 99%
See 1 more Smart Citation